Asociación Thysanoptera (Insecta)- Vicia faba (Fabaceae) en la Prepuna y Puna de Jujuy, Argentina - Zamar, María Inés; Neder de Román, Lilia Estela (Revista de Biología Tropical, 2012)
Thysanoptera (Insecta)-Vicia faba (Fabaceae) association in Prepuna and Puna in Jujuy, Argentina. The different phenological stages of Vicia faba provide food resources and substrates for the development of a significant diversity of insects. This study aimed to identify the complex of anthophyllous thrips, analyze the species population fluctuations, to obtain some bioecological aspects and the role they play in this association. The study and sampling was conducted during the flowering-fruiting bean crop stages in two phy- togeographical regions of Jujuy: Prepuna (2 479m asl) on a weekly basis, from October-December 1995-1996 and Puna (3 367m asl) every two weeks, from December 2007-March 2008. Each sample consisted of 25 flowers taken at random; only at Prepuna a complementary sampling of three hits per plant (n=10 plants) was conducted. Observations were made on oviposition sites, admission to the flower, pupation sites, feeding behavior and injuries caused. In Prepuna, the Thysanoptera complex consisted of Frankliniella australis, F. occidentalis, F. gemina, F. schultzei and Thrips tabaci; in Puna, the specific diversity was restricted to F. australis and F. gemina. Although the planting-harvest period in both areas did not match, the fluctuations in populations showed the same pattern: as flowering progressed, the number of thrips coincided with the availability of food resources. In both areas, F. australis was the dominant species and maintained successive populations; it layed eggs in flower buds, and larvae hatched when flowers opened; feeding larvae and adults brought about silvery stains with black spots. In Prepuna, F. australis went through the mobile immature stages on flowers, while quiescent stages were on the ground; in the Puna, all development stages took place within the flowers. Thrips tabaci, F. shultzei, F. occidentalis and F. gemina were temporary and opportunistic in Prepuna, while the presence of F. gemina was sporadic in Puna. The number of Thysanoptera species associated with beans cultivation in Argentina has increased.